Absolute pitch and its implications for music - Ken'ichi MIYAZAKI (Archives of Acoustics, 2014)
Absolute pitch is defined as an ability to identify musical pitch of single tones presented in isolation. There has been so far little empirical research investigating in detail how people with absolute pitch perceive musical pitch, so absolute pitch is still surrounded by mystery. This article summarizes a series of the author's experiments exploring the perception of musical pitch and melodies by listeners having absolute pitch. Absolute pitch has been considered an important part of musical ability, and is assumed to be acquired primarily through early music training at the age from 3 to 6 years. However, critically important is relative pitch (pitch relations) on which melodies and harmonic structures are constructed. In contrast, absolute pitch that enables its possessors to name isolated tones is not crucial to music. Moreover, the experimental findings suggest that absolute pitch may sometimes be disadvantageous for musicians since it may, in some cases, be incompatible with processing and learning of relative pitch.